Active thermal control for modular power converters in multi-phase permanent magnet synchronous motor drive system - Yan, Hao; Zhao, Weiduo; Buticchi, Giampaolo; Gerada, Chris (2021)
Modular winding structure has been employed in the Permanent Magnet Synchronous Motors (PMSMs) to increase the reliability and reduce the torque ripple. Nevertheless, the reliability of the motor system depends on the lifetime of the power semiconductor devices. Since the thermal cycles, which can generate the mechanical stress between the different material layers in power devices, are the key factors to influence the lifetime of power devices, in this paper, an Active Thermal Control (ATC) for modular power converters in PMSM drive is proposed to extend the system lifetime. The power routing method is employed to balance the power in a quadruple modular winding PMSM system. The Rainflow Counting Algorithm is used to calculate the thermal cycles with a load mission profile, and estimate the lifetime of the power converters. The proposed method is validated by both simulation and experiments.